PASANG SURUT PERPOLITIKAN ISLAM DALAM KANCAH SEJARAH - Mansur (UIN Mataram, 2018)
This paper discusses the ups and downs of Islamic politics in the historical arena, the politics referred to in this paper is photographing the history of politics at the time of the Caliph or Companions and politics in the history of Islam. Political Islam is often seen as a combination of